Tumor size, tumor location, and antitumor inflammatory response are associated with lymph node size in colorectal cancer patients - Rössler, Ortrun; Betge, Johannes; Harbaum, Lars; Langner, Cord (Modern pathology, 2017)
Lymph node size affects lymph node retrieval in surgical specimen and is used as criterion for pre-operative radiological estimation of metastatic disease. However, factors determining lymph node size remain to be established. Therefore, the association between lymph node size and presence of metastatic cancer deposits as well as different primary tumor characteristics was analyzed in a prospective cross-sectional study. Visible and palpable nodes were harvested, and conventional histology, immunohistochemistry, and molecular analysis were performed. The study cohort comprised 148 patients (median age 69 years, range 36-92). Lymph node dissection rendered 4167 nodes. Mean lymph node count was 28 (median 26, range 9-67). Metastatic disease was detected in 320 (8%) nodes and was associated with lymph node size (P<0.001). Positive nodes measuring ≤2 mm caused upstaging within the N category in one third of cases, but did not identify patients as node-positive as all patients also had positive larger nodes. Large tumor size (P=0.001), right tumor location (P<0.001), and deep tumor penetration (P=0.024) were all independently associated with lymph node size, whereas high lymphocytic antitumor reaction just missed statistical significance (P=0.053) in multivariable analysis. Microsatellite instability had no influence on lymph node size when analysis was restricted to right-sided tumors. In conclusion, analysis of small lymph nodes may lead to upstaging within the N category, but they do not identify a patient as node-positive and do therefore not influence clinical decision-making in the adjuvant setting. The majority of enlarged lymph nodes, including those measuring >1 cm, are not involved by cancer. Different tumor characteristics, such as large primary tumor size, right tumor location, and deep tumor penetration are independently associated with lymph node size and need to be considered when interpreting enlarged nodes detected by radiological imaging.
Gesehen am 25.04.2018